2016
DOI: 10.1090/tran/6844
|View full text |Cite
|
Sign up to set email alerts
|

Derivative bounds for fractional maximal functions

Abstract: In this paper we study the regularity properties of fractional maximal operators acting on BVfunctions. We establish new bounds for the derivative of the fractional maximal function, both in the continuous and in the discrete settings.Question A. (Haj lasz and Onninen [10]) Is the operator f → |∇M f | bounded from W 1,1 (R d ) to L 1 (R d )?A standard dilation argument reveals the true nature of this question: whether the variation of the maximal function is controlled by the variation of the original function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 16 publications
(39 reference statements)
1
74
2
Order By: Relevance
“…The problem of finding the sharp constant in this inequality is certainly an interesting one. The strategy of [9] to prove Theorem 5.2 in the pure fractional case β > 0 is very different from that of the proof of Theorem 3.1. While in the proof of Theorem 3.1 the essential idea is to prove that the maximal function does not have any local maxima in the set where it disconnects from the original function, in the fractional case β > 0, the mere notion of the disconnecting set is ill-posed, since one does not necessarily have M β (f )(x) ≥ |f (x)| a.e.…”
Section: Maximal Operators Of Convolution Typementioning
confidence: 98%
See 1 more Smart Citation
“…The problem of finding the sharp constant in this inequality is certainly an interesting one. The strategy of [9] to prove Theorem 5.2 in the pure fractional case β > 0 is very different from that of the proof of Theorem 3.1. While in the proof of Theorem 3.1 the essential idea is to prove that the maximal function does not have any local maxima in the set where it disconnects from the original function, in the fractional case β > 0, the mere notion of the disconnecting set is ill-posed, since one does not necessarily have M β (f )(x) ≥ |f (x)| a.e.…”
Section: Maximal Operators Of Convolution Typementioning
confidence: 98%
“…This shows that the map f → |∇M β f | is bounded from W 1,1 (R d ) to L q (R d ) in this case. We are thus left with the following endpoint question, first posed in [9]. |f…”
Section: Maximal Operators Of Convolution Typementioning
confidence: 99%
“…Inequality (14) is not optimal, and it was asked in [29] whether the sharp constant for inequality (14) is in fact = 2; this question was resolved in the affirmative by Madrid in [31]. Later on, the above results were extended to a fractional case in [17,32,33], to a one-sided case in [7], and to a high dimensional case in [34]. For other interesting works we can consult [19,20,[35][36][37].…”
Section: Theorem 1 M + 2 Is Bounded and Continuous Frommentioning
confidence: 99%
“…Notice that the constant = 1 in inequality (2) is sharp. Recently, inequality (2) was extended to a fractional setting in [17,Theorem 1] and to a multisublinear fractional setting in [18, Theorems 1.3-1.4]. In the centered setting, Kurka [12] showed that if is of bounded variation on R, then inequality (2) holds for M (with constant = 240, 004).…”
Section: Introductionmentioning
confidence: 99%
“…This question was investigated by Luiro [28] and later extensions were given in [7,21,29]. More interesting works related to this topic may be found in [2,5,6,8,13,22,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%